The Influence of Organizational Culture on Employee Work Performance at the Doloksanggul Sub-District Office, Humbang Hasundutan Regency - Lin Shui Sinurat; Herta Manurung (Jurnal Mantik, 2021)
This study aims to analyze how the influence of organizational culture on employee work performance at the Doloksanggul Sub-District Office, Humbang Hasundutan Regency. The data analysis method used is simple correlation analysis method, simple linear regression analysis and t test. The sample in this study were all employees of the Doloksanggul Sub-district Office, Humbang Hasundutan Regency as many as 30 people. Data obtained from the questionnaire distributed to a sample of 30 people obtained a correlation with the result that rcount (0.756)> rtable (0.374) concluded that there was a significant relationship between culture. Organization (X) with Employee Performance (Y) at the Doloksanggul Sub-District Office, Humbang Hasundutan Regency. Based on table 3.2 Guidelines for Interpretation of Correlation Coefficients, the coefficient found is 0, 756 was in the strong category. So there is a strong relationship between Organizational Culture (X) and Employee Work Performance (Y) at the Doloksanggul Sub-District Office, Humbang Hasundutan Regency. R Square is 0.571 or 57.10%. This shows that the influence of Organizational Culture (X) with Employee Work Performance (Y) at the Doloksanggul Sub-District Office, Humbang Hasundutan Regency is 57.10% and the remaining 42.90% is influenced by other factors not discussed in this study. The regression equation is Y = 4.539 + 0.502X. The regression equation above can be explained that if Organizational Culture or X = 0 then the value of Employee Work Performance or Y will increase by 4.539. The significance of variable correlation is 6.110. Then the value is compared with t table with an error rate of 5% df = n-2 = 28. The t table value is 2.048. In accordance with the requirements of testing the hypothesis that t count (6.110)> t table (2.048) it can be concluded that Organizational Culture (X) has a positive and significant influence on Employee Work Performance (Y) at the Doloksanggul Sub-District Office, Humbang Hasundutan Regency, the research hypothesis is accepted.